Campuran pemasaran dan ekuiti jenama halal keseluruhan - Ahmad Sabri, Yusuff (2017)
The main objective of this study was to examine and identify the factors that affect halal brand equity through the marketing lens. This study investigated factors such as advertising, pricing, company reputation, environmental turbulence with brand equity dimensions which are halal brand association, brand loyalty, perceived quality and halal brand equity which have not been given much research attention. In particular, the goal of this study was to determine how marketing efforts such as marketing elements, namely advertising, price, company reputation and environmental turbulence affect halal brand equity dimensions and how they affect or develop the overall halal brand equity. This was a quantitative study where a survey methodology was employed to collect the data. Individual consumers, were chosen as the sample for this study. The systematic sampling technique and intercept procedure were used to select respondents from individuals who shopped at four Hyper markets in the Klang Valley. Twenty- four main hypotheses were proposed to influence halal brand equity, but only ten hypothesis were supported. Structured questionnaires comprising 65 items were used to measure the variables; halal brand equity, marketing mix, company reputation and environmental turbulence were adopted in this study. The findings revealed that significant relationships exist among the variables (marketing mix; advertising, company reputation, environmental turbulence and halal brand equity) with halal brand equity. The findings also revealed that environmental turbulence moderated the relationships between perceived quality and halal brand equity, and perceived quality mediated fully the relationship between advertisement and halal brand equity. In conclusion, this study enhances the theories and models introduced such as the tawhidic paradigm, customer- based brand equity, the brand equity creation process model, servicedorminant logic and the contingency theory put together.